Women’s experiences of gender-based violence supports through an intersectional lens: a global scoping review - Amaya Perez-Brumer; Beverley M Essue; Cyndirela Chadambuka; Isabel Arruda-Caycho; Danielle Tocallino; Rebecca Balasa; Prossy Kiddu Namyalo; Carmina Ravanera; Sarah Kaplan (BMJ Public Health)
Objective To apply an intersectional lens to explore how the interconnected social identities of women across global settings impact access experiences for gender-based violence (GBV) supports.Design A scoping review.Data sources We systematically searched seven databases to identify studies published in English from the database inception to January 2023.Inclusion criteria We included peer-reviewed studies with a primary objective of examining the access experiences of populations who self-identify as women (aged 15 years or older) who have experienced GBV, have intersecting identities (ie, racialisation, poverty, etc) that can further contribute to marginalisation and utilised or sought support services.Methods Two reviewers independently completed title/abstract, full-text screening and data charting. Integrating intersectionality theory and the McIntyre access framework, we analysed support service access and utilisation across social identities, axes of marginalisation and geographic contexts.Results 210 papers (195 distinct studies) met the inclusion criteria. Most studies (60%) were published since 2015 and used qualitative methods (63%). Findings reflected intersectional differences in women’s experiences of accessing GBV services across contexts and lived experiences. Common findings indicate that seeking GBV support was motivated and enabled by informal supports and positive prior experiences in accessing services. However, findings highlight that structural and systemic constraints in existing support systems (in all study settings) impact access to necessary support services and their alignment with women's needs. Few studies examined health and non-health outcomes associated with unhindered access to care.Conclusions Women’s experiences with GBV support systems in different geopolitical contexts highlight barriers across axes of racialisation, poverty, multidimensional violence and other systemic factors, which are often eclipsed in generic one-size-fits-all models of support. This research can inform transformational policy development and tailored interventions to improve outcomes for all women who experience GBV and thus advance gender equality and equity goals.